Anaerobic co-digestion of rice straw and digested swine manure with different total solid concentration for methane production - Darwin, Darwin; Cheng, Jay J.; Liu, Zhimin; Gontupil, Jorge; Kwon, O-Seob (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: This study aimed to investigate potential methane production through anaerobic co-digestion of rice straw and digested swine manure with different total solids. The research was carried out in bench scale with utilizing batch system. To evaluate the stability of anaerobic co-digestion process, the experiment was run in triplicate. The anaerobic co-digestion process was operated in 500 mL batch digesters under constant agitation speed and temperature. The agitation speed was maintained at 270 r/min. Temperature of the batch system was set and maintained at 35oC. Digested swine manure utilized in this experiment was obtained from semi-continuous digesters run at steady state condition, with 25 days of hydraulic retention time under mesophilic condition. Rice straw (RS) generated the highest methane production at 3% total solids (TS) which was around (1814±47.43) mL, where in this concentration, it had C:N ratio at 10.6:1. Rice straw obtained the highest methane yield at 3% TS, which was around (141.4±3.70) mL CH4/g volatile solids (VS) added. Rice straw also had the highest chemical oxygen demand (COD) removal and VS reduction at 3% TS which were around (52.97%±1.46%) and (61.81%±1.04%), respectively.Keywords: anaerobic co-digestion, rice straw, digested swine manure, methane productionDOI: 10.3965/j.ijabe.20140706.010Citation: Darwin, Cheng J J, Liu Z M, Gontupil J, Kwon, O S. Anaerobic co-digestion of rice straw and digested swine manure with different total solid concentration for methane production. Int J Agric & Biol Eng, 2014; 7(6): 79－90.